Teaching Through Sand: Creative Applications of Sandtray Within Constructivist Pedagogy. Issue 3 (3rd July 2019) - Saltis, Michelle N.; Critchlow, Claire; Smith, Jennifer A.
ABSTRACT: This article applies principles of sandtray within constructivist pedagogy for counselor educators. Beginning with an overview of sandtray and creativity within counseling and supervision, the authors make recommendations for the use of sandtray in coursework for counselors-in-training. The asserted approach focuses on student growth through increasing tolerance of ambiguity, an essential skill for counselors.